Heat and mass distribution by mixed convection in an unsteady power law fluid over an accelerated riga plate under the influence of heat generation/absorption and thermal radiation - Adeyemi, A.A.; Olajuwon, B.I.; Sogbetun, L.O.; Iyoko, M.O.; Raji, M.T.; Fagbemiro, O.; Adejumobi, I. A. (International Journal of Mathematical Analysis and Modelling, 2026)
The significance of heat generation/absorption, thermal radiation, inclination angle and chemical reaction on the convective heat and mass transfer in a power law fluid over an accelerated Riga plate is examined. This study investigates the non-Newtonian power law index for the cases when (pseudo-plastic fluid), and (dilatant fluid). The Grinberg term incorporated into the momentum equation is utilized to express the Riga plate. By employing suitable transformation technique, related non-linear partial differential equations formulated are converted to ordinary differential equations. The resulting similarity equations are solved numerically by employing shooting method embedded in Matlab computational software. Graphs are utilized to illustrate the impact of fluid variables entering the velocity, temperature, and concentration profiles. Further, numerical outcomes of the combined effects of thermal radiation, chemical reaction and heat generation on the skin friction coefficients, heat transfer rate and mass transfer rate are tabulated and analysed. The results disclose contribution of sundry parameters on the fluid flow, mass and heat transfers.